Possible Study of Drug-Drug Interactions between Lisinopril and Gliclazide in Experimental Animals - AL-mohamadi, Ahmed A.; Ibrahim, Doa'a Anwar (Journal of Drug Discovery and Therapeutics, 2015)
The most often problem in type II diabetic patients coexists with hypertension, the incidence of hypertension among diabetic patients is high. In this case, use a combination of medicine unavoidable (Polypharmacy). In such situations, this may be leading to drug-drug interactions. Gliclazide (sulphonylurea) and lisinopril (ACE inhibitors) widely used in Type II diabetes associated with hypertension. The present study was aimed to evaluate the presence of any drug-drug interaction features between single and multiple dose treatment of lisinopril (1mg/kg) on antidiabetic activity of gliclazide (3.7 mg/kg) in both normal and streptozotocin induced diabetic rats and in normal rabbits. Selected doses of gliclazide, lisinopril and their combination given to animals via oral route with one week washout periods in between treatments. The blood samples were collected from rats and rabbits at different time intervals 0, 4, 8, 12, 16, 20, and 24 hours and were investigated for serum glucose and insulin level by GOD/POD and insulin levels kits. Gliclazide was produced a significant effect on blood glucose reduction in multiple doses treatment of lisinopril and gliclazide in normal and diabetic rats, whereas, single dose treatment was produced a significant effect on blood glucose in diabetic rats only, in combination, chronic use of lisinopril increases the effect of gliclazide in normal and diabetic rats. Thus, it can be concluded that lisinopril and gliclazide maybe ought to be avoidable or may need dose adjustment when used concomitantly. However, further studies are necessary.